2017
DOI: 10.1002/jcp.25852
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of ER stress and unfolded protein response pathways in skeletal muscle health and disease

Abstract: Skeletal muscle is the most abundant tissue in the human body and can adapt its mass as a consequence of physical activity, metabolism, growth factors, and disease conditions. Skeletal muscle contains an extensive network of endoplasmic reticulum (ER), called sarcoplasmic reticulum, which plays an important role in the regulation of proteostasis and calcium homeostasis. In many cell types, environmental and genetic factors that disrupt ER function cause an accumulation of misfolded and unfolded proteins in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
199
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(208 citation statements)
references
References 117 publications
(174 reference statements)
8
199
0
1
Order By: Relevance
“…A sensitive increase in temperature (40-46°C) can cause protein unfolding, entanglement, and aggregation, and further induce ER stress [27]. ER stress was induced with increased eIF2α phosphorylation and XBP1 splicing, resulting in the increased expression of GADD34, CHOP and BiP genes [14, 28]. We obtained similar ER stress responses in heat-treated 16HB140 cells.…”
Section: Discussionsupporting
confidence: 57%
“…A sensitive increase in temperature (40-46°C) can cause protein unfolding, entanglement, and aggregation, and further induce ER stress [27]. ER stress was induced with increased eIF2α phosphorylation and XBP1 splicing, resulting in the increased expression of GADD34, CHOP and BiP genes [14, 28]. We obtained similar ER stress responses in heat-treated 16HB140 cells.…”
Section: Discussionsupporting
confidence: 57%
“…In contrast with rodent data, here we have demonstrated that a short training program based on repeated high‐intensity exercise reduced the SLN protein levels in vastus lateralis despite eliciting much less total energy expenditure than the 4‐day walking intervention. A principal difference between prolonged walking and repeated 30‐second all‐out sprints is the marked metabolic disturbances evoked by the sprints, which cause substantial lactic acidosis, oxidative stress, and sarcoplasmic reticulum stress . Endoplasmic reticulum stress reduces SLN expression in C2C12 cells .…”
Section: Discussionmentioning
confidence: 81%
“…Protein turnover and removal of misfolded and poly-ubiquitinated proteins are predominately accomplished by 2 degradation machineries, the ubiquitin-proteasome system (UPS) as well as the autophagy and lysosome system [13]. Dysfunction of either of these proteolytic machineries has been implicated in the onset and progression of striated muscle as well as neurodegenerative diseases [4,5,6]. In this context, point mutations in VCP/p97 (valosin containing protein) were shown to cause inclusion body myopathy associated with Paget disease of the bone and frontotemporal dementia (IBMPFD) and amyotrophic lateral sclerosis (ALS).…”
Section: Introductionmentioning
confidence: 99%